Analisis Kelayakan Potensi Ekowisata Pantai Pandan, Kecamatan Pandan Tapanuli Tengah Sumatera Utara. - Wenny Aberti Manurung; I Wayan Restu; Gde Raka Angga Kartika (Bumi Lestari Journal of Environment, 2022)
Abstract This study was conducted in Pandan Beach, Pandan District, Central Tapanuli, North Sumatra which aims to know the supporting factors of coastal tourism feasibility from the limiting factors of tourism conformity index value and to know the tourism conformity index (IKW). This research was conducted for 1 Month, namely in early March to early April 2021. The method used in this study is descriptive quantitative method. Determination of the location of research based on the representation of the area is located with the consideration that in the area is often carried out tourist activities such as point 1 waterspot activities, point 2 is swimming activity and point 3 ship activity that carries passengers around the island. parameters measured in the Index of Tourism Conformity Category Of Beach Tourism namely depth, tipe beach, beach width, water base material, beach slope, current speed, brightness, closure of coastal land, hazardous biota, and availability of fresh water. Based on the observation of the potential of Pandan Beach is the white sand, the waves are not too besar. The results showed the value of tourist conformity index of the three stations, namely at station 1 has a value of 2,695, while at stations II and III has the same value of 2,795. It shows that pandanus beach falls into the category of very appropriate (SI) with a conformity index value of >2.5. Hal showed that Pandan Beach Tapanuli Central North Sumatra has a very good potential to be a location for recreational beach tourism activities. Keywords: Potential; Tourism Conformity Index; Pandan Beach.